FRI0498 An mri study of bone erosions healing in the wrist and metacarpophalangeal joints of patients with rheumatoid arthritis. (23rd January 2014) - Barbieri, F.; Tomatis, V.; Zampogna, G.; Fabbro, E.; Piccazzo, R.; Ferrero, G.; Cimmino, M. A.
Abstract : Background: Bone erosions have been always considered the hallmark of rheumatoid arthritis (RA). Advanced imaging techniques, such as computed tomography, MRI, and, at least in several joint areas, ultrasonography have shown increased sensitivity for demonstration of erosions in comparison with conventional radiography. In addition, modern follow-up of erosions requires high sensitivity to change in view of the increased capability of new therapeutic strategies to promote their improvement. Erosions healing in patients with RA is considered exceptional when studied by conventional radiology. Modern and sensitive imaging techniques can appreciate more subtle changes of bone morphology due to their multiplanar capacity. Objectives: This study is concerned with an extremity-dedicated MRI evaluation of erosion changes in patients with RA followed over time. Methods: 57 patients affected by RA (42 women, median age 52 years, range 20-73 years, median disease duration 22 months, range 1-420 months) diagnosed according to the 1987 revised ACR criteria were studied. Wrist and metacarpophalangeal (MCP) joints were imaged with a dedicated-extremity, 0.2 T MRI (Artoscan, Esaote, Genova, Italy) at baseline and after a median of 15 months (range 6-121 months). A turbo T1-weighted three dimensional sequence (T3-D T1) in the coronal plane, with subsequent multiplanar reconstructions on the axial and sagittal planes was used; slice thickness was 0, 3 mm, TR 860 ms, TE 26 ms, and number of excitations (NEX) 1. Bone studied included the 2 nd to 5 th MCPs, the 1 st to 5 th metacarpal bases, the 8 wrist bones, and the distal radius and ulna. Erosions were scored according to the RAMRIS. Results: 30/57 (52.6%) patients were RF positive and 34/57 (59.6%) anti CCP positive. Median ESR was 40 mm/h (range 7-120 mm/h) and median CRP was 6.9 mg/dL (range 0.6-128 mg/dL). A decrease of the RAMRIS erosion score, indicating erosion healing, was seen in 7 (12.3%) patients at the wrist and in 3 (5.3%) at the MCPs. The same figures in patients with unchanged and worsened RAMRIS were 17 (29.8%) and 31 (54.4%), and 33 (57.9%) and 17 (29.8%), respectively. Altogether 1311 bones were evaluated (855 wrist and 456 MCP bones). A decrease of at least one point in the RAMRIS for erosions was observed in 27 (3.2%) wrist bones and in 7 (1.5%) MCPs. The bones with more frequent healing were 2 nd metacarpal basis (0.7%), triquetrum (0.6%), 2 nd (0.5%) and 5 th (0.74%) metacarpal heads. 3 patients with improved global RAMRIS had, however, worsening of the erosions in at least one wrist bone. 3 patients with unchanged RAMRIS and 7 with worsening RAMRIS had erosion healing in at least one wrist bone. The same finding was observed at the MCPs level in 2 and 1 patients, respectively. Finally 5 patients with unchanged RAMRIS had worsening of the erosions at the wrist and 2 patients at the MCPs. Conclusions: Healing of erosions occurs, although rarely, in patients with RA when studied with sensitive imaging techniques, such as MRI. The coexistence of erosion's healing and deterioration in the same hand or even in the same bone was frequent, supporting the view that not only general disease activity but also localized inflammatory and mechanical mechanisms are important. Disclosure of Interest: None Declared